Risks and security of internet and systems : 11th International Conference, CRiSIS 2016, Roscoff, France, September 5-7, 2016, Revised selected papers /: 11th International Conference, CRiSIS 2016, Roscoff, France, September 5-7, 2016, Revised selected papers. (2017) - Unknown
No abstract available